2015
DOI: 10.12681/mms.1171
|View full text |Cite
|
Sign up to set email alerts
|

Mesozooplankton biomass and abundance in Cyprus coastal waters and comparison with the Aegean Sea (eastern Mediterranean)

Abstract: Here we conduct the first comprehensive assessment of mesozooplankton abundance, biomass, and taxa composition in Cyprus coastal waters (Levantine Sea). Mesozooplankton abundance and biomass sampled at several locations around the island ranged from 153 -498 individuals m -3 and 0.7 -5.2 mg dry weight m -3 , respectively, with significantly larger biomass observed in winter-early spring (March) than in summer (September). The community was dominated by calanoid and cyclopoid copepods throughout the year (80% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
9
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
7
9
2
Order By: Relevance
“…The present abundance values for the total mesozooplankton present certain similarities with the reports of Hannides et al (2015) for the same area, though the elevated abundance in spring that was found by the latter was not recorded in the samples from this season in any of the three years. In contrast to the present investigation, where the vertical zooplankton tows were conducted in the 0-50 m depth range, the average tow depth was about 100 m in the study of Hannides et al (2015).…”
Section: Total Mesozooplanktonsupporting
confidence: 88%
See 2 more Smart Citations
“…The present abundance values for the total mesozooplankton present certain similarities with the reports of Hannides et al (2015) for the same area, though the elevated abundance in spring that was found by the latter was not recorded in the samples from this season in any of the three years. In contrast to the present investigation, where the vertical zooplankton tows were conducted in the 0-50 m depth range, the average tow depth was about 100 m in the study of Hannides et al (2015).…”
Section: Total Mesozooplanktonsupporting
confidence: 88%
“…The present abundance values for the total mesozooplankton present certain similarities with the reports of Hannides et al (2015) for the same area, though the elevated abundance in spring that was found by the latter was not recorded in the samples from this season in any of the three years. In contrast to the present investigation, where the vertical zooplankton tows were conducted in the 0-50 m depth range, the average tow depth was about 100 m in the study of Hannides et al (2015). Considering these differences in the sampling depths and that in the oligotrophic area of the eastern Mediterranean the mesozooplankton abundance decreases under the 0-50 m depth stratum (Mazzocchi et al, 1997;Ramfos et al, 2006), direct comparisons between the present study and that of Hannides et al (2015) must be taken with caution.…”
Section: Total Mesozooplanktonsupporting
confidence: 88%
See 1 more Smart Citation
“…Water circulation around Cyprus is complex and influenced by permanent, transient and recurrent circulation features. According to Hannides et al (2015) [47], the mesozooplankton along the southern coasts of Cyprus (Amathounta, Meneou and Protaras) is primarily influenced by the eastward branch of the Mid-Mediterranean Jet, as well as by eddies and local current systems that form south of the island. In contrast, along the northwest coast of Cyprus (Latsi), the mesozooplankton is influenced by the westward-moving Asia Minor Current and associated local flow phenomena [48].…”
Section: Discussionmentioning
confidence: 99%
“…In its eastern part, the Levantine Sea's ultra-oligotrophic nature limits productivity even further [2][3][4]. In such oligotrophic environments, highly diverse fouling communities are of extreme importance in the transfer of energy from primary production to higher biological levels [5].…”
Section: Introductionmentioning
confidence: 99%